Efek tebal lapisan soil layer over a horizontal rigid basesoil model pada respon inelastik struktur bangunan. - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Studi Kawasan dan Pedesaan Universitas Gadjah Mada, 1999)
ABSTRAK There are several soil models in the Lumped Parameter Methods that can be used in the structural analysis to consider the interaction between the soil and foundation. One of the model is a soil layer over the horizontal rigid base. The stiffness dan damping of the soil-foundation interaction are affected by thickness of the soil layer. Thickness of the soil layer, therefore, will influence the stiffness of the structural system. Research on the effects of soil thickness on the inelastic response of building structure need to be carried out. Research on the effects of soil thickness on the inelastic response of frame-wall structure has been conducted. The selected building model was an earthquake load dominated 12-storey reinforced concrete frame-wall structure. The standard soil properties, compressive concrete strength and steel yield strength data have been used. Three types of soil, respectively were 10 meter, 20 meter and 30 meter thick have been considered. The elastic homogeneous half-space soil model has also been used to compare with the soil models considered. The 1966 Parkfield earthquake N65E horizontal component was used as the input motion. Result of the research shows that a slight lengthening of the structural fundamental period is due to the increase of the soil thickness. The soil thickness does not significantly affect the foundation rotations, vertical displacment of the foundation's tip, wall moment envelopes, curvature ductility demand, energi dissipation and element damage index. The effects of the soil properties are more significant than the effects of the soil thickness.